Challenges and Opportunities of State Religious College in the Digital Era - Tulung, Jeane Marie; Berdame, Jekson; Lapian, Alrik; Wuwung, Olivia Cherly; Gerung, Farno Billy Arthur (Budapest International Research and Critics University, 2021)
The development of science produces increasingly sophisticated technology. Then the developing technology affects human efforts in knowledge. The movement of universities in many aspects cannot be separated from the developing technology. No exception State Religious Universities (PTKN) in Indonesia are also under the influence of technological advances. This paper discusses the challenges and opportunities of State Religious Universities in the digital era. In addition to the challenges that inevitably arise in every era of change, what must be welcomed creatively and innovatively are the opportunities available with wise use of technology. This paper concludes that digital technology opens space for democratic knowledge development.